The Role of MicroRNAs in Skin Fibrosis - Babalola, Olubukola (2013)
Fibrotic skin disorders may be debilitating and impair quality of life. There are few effective treatment options for cutaneous fibrotic diseases. In this review, we discuss our current understanding of the role of microRNAs (miRNAs) in skin fibrosis. MiRNAs are a class of small, noncoding RNAs involved in skin fibrosis. These small RNAs range from 18 to 25 nucleotides in length and modify gene expression by binding to target messenger RNA (mRNA), causing degradation of the target mRNA or inhibiting the translation into proteins. We present an overview of the biogenesis, maturation and function of miRNAs. We highlight miRNA’s role in key skin fibrotic processes including: transforming growth factor (TGF)-beta signaling, extracellular matrix (ECM) deposition, and fibroblast proliferation and differentiation. Some miRNAs are profibrotic and their upregulation favors these processes contributing to fibrosis, while antifibrotic miRNAs inhibit these processes and may be reduced in fibrosis. Finally we describe the diagnostic and therapeutic significance of miRNAs in the management of skin fibrosis. The discovery that miRNAs are detectable in serum, plasma, and other bodily fluids, and are relatively stable, suggests miRNAs may serve as valuable biomarkers to monitor disease progression and response to treatment. In the treatment of skin fibrosis, antifibrotic miRNAs may be upregulated using mimics and viral vectors. Conversely, profibrotic miRNAs may be downregulated by employing anti-miRNAs, sponges, erasers and masks. We believe that miRNA-based therapies hold promise as important treatments and may transform the management of fibrotic skin diseases by physicians.